2022
DOI: 10.1007/s41999-021-00595-0
|View full text |Cite
|
Sign up to set email alerts
|

A scoping review of the changing landscape of geriatric medicine in undergraduate medical education: curricula, topics and teaching methods

Abstract: Purpose The world’s population is ageing. Therefore, every doctor should receive geriatric medicine training during their undergraduate education. This review aims to summarise recent developments in geriatric medicine that will potentially inform developments and updating of undergraduate medical curricula for geriatric content. Methods We systematically searched the electronic databases Ovid Medline, Ovid Embase and Pubmed, from 1st January 2009 to 18th … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 88 publications
(122 reference statements)
0
16
0
1
Order By: Relevance
“…Communicating with older adults about self-management requires a healthcare workforce with a strong understanding tion, mentation, and mobility) for an age-friendly health system, may also be a viable alternative for preparing healthcare professionals (Hawley et al, 2021). Health care preparation also requires communication skills, empathy, and professionalism (Gellis et al, 2019;Masud et al, 2022). Engaging caregivers of older adults is also a best practice for IPE curricula (Farrell et al, 2018).…”
Section: Case Study #3mentioning
confidence: 99%
“…Communicating with older adults about self-management requires a healthcare workforce with a strong understanding tion, mentation, and mobility) for an age-friendly health system, may also be a viable alternative for preparing healthcare professionals (Hawley et al, 2021). Health care preparation also requires communication skills, empathy, and professionalism (Gellis et al, 2019;Masud et al, 2022). Engaging caregivers of older adults is also a best practice for IPE curricula (Farrell et al, 2018).…”
Section: Case Study #3mentioning
confidence: 99%
“…Although geriatric medicine has long been incorporated into the medical curriculum in some western countries, it is still in its early integration stage in most medical schools, specifically in the Asian region. The challenges in incorporating geriatric medicine into the medical curriculum are multidimensional -expanding a fully packed curriculum, resentment from maximally loaded faculty staff, shortage of trained teaching geriatricians, [10][11][12][13][14] and the administration's dilemma for salary adjustment. Furthermore, on the attitude of students towards the aged [11,[15][16][17][18], Bagri and Tiberius reported that students had not felt appropriately engaged in geriatrics, despaired at the futility of care, and were depressed and frustrated by the decline and death of their patients.…”
Section: Challenges and Solutions In Establishing Geriatric Medicine ...mentioning
confidence: 99%
“…The challenges in incorporating geriatric medicine into the medical curriculum are multidimensional -expanding a fully packed curriculum, resentment from maximally loaded faculty staff, shortage of trained teaching geriatricians, [10][11][12][13][14] and the administration's dilemma for salary adjustment. Furthermore, on the attitude of students towards the aged [11,[15][16][17][18], Bagri and Tiberius reported that students had not felt appropriately engaged in geriatrics, despaired at the futility of care, and were depressed and frustrated by the decline and death of their patients. [19] The problem of non-geriatricians teaching Geriatrics has been addressed through various approaches.…”
Section: Challenges and Solutions In Establishing Geriatric Medicine ...mentioning
confidence: 99%
See 1 more Smart Citation
“…This marked curriculum transformation has afforded an opportunity to both innovate and evaluate undergraduate education in geriatric medicine, which will provide one model for teaching on aging, complementing the work of the European Geriatric Medicine Society [ 5 ]. We anticipate that by providing this high-quality education in geriatric medicine, we will equip and inspire physicians of the future with the expertise, knowledge and skills needed to care for the unique and complex needs of older people.…”
Section: Introductionmentioning
confidence: 99%